PENGARUH PELATIHAN TERHADAP KINERJA GURU SEKOLAH DASAR DI MARO SEBO KABUPATEN MUARO JAMBI - Rauda Tuljannah; Kasiono Kasiono (Universitas Batanghari Jambi, 2023)
This study aims to find out the implementation of this study aims to determine the description and influence training on the performance of elementary schools teachers in Maeo Sebo, Muaro Jambi Regency. By taking samples from 2 elementary schools in Maro Sebo District Muaro Jambi. This type of research used quantitative research with 40 research subjects, which were conducted in two schools namely SD Negeri 38 and MIN 1 in Maro Sebo, Muaro Jambi Regency. In this study using data collection techniques through questionnaires, Processing data analysis using the classic assumption test, namely the normality test, and homogeneity test as well as verification analysis with simple linear regression. The results showed that t value of the training variabel (X) on teachers performance (Y) is 2,752 with a sig. 0,008. This means that t count > t table. In other words. o is rejected and H is accepted because 0,000 < 0,005. This means that the result of this t test indicate that training (X) has a positive and significant effect on the performance of elementary school teachers in Maro Sebo, Muaro Jambi Regency. Keywords : Training, Teacher Performance